Drinking in a Micro-Perspective: The Role of Engagement in Imitation of Sips of Alcoholic Beverages. Issue 3 (July 2013) - Larsen, Helle; Lichtwarck-Aschoff, Anna; Kuntsche, Emmanuel; Granic, Isabela; Engels, Rutger C. M. E.
In the current study, we used a real-time approach to test whether engagement during an interaction was related to imitation of another person's drinking behaviour. We observed moment-to-moment engagement levels and sipping behaviour during a 30 minute interaction between same-sex confederates and participants in a semi-naturalistic ad lib drinking context (N = 34 dyads; 18 males; 18–25 years). We applied multilevel proportional hazard models to test the relationships between engagement levels and imitation of sipping, when consuming alcohol compared to soda. Results showed that engagement levels were not related to the propensity to imitate sipping. Whether the dyad consumed alcoholic or non-alcoholic beverages did not moderate the associations between engagement and imitation of sipping.